From Exclusion to Empowerment: Financial Inclusion as a Catalyst for Socio-economic Development Among Rural Youth Entrepreneurs - Israel, Baraka (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2024)
This study examines how financial inclusion (FNI) influences the socio-economic status and empowerment of rural youth entrepreneurs. Data for the study was collected using a cross-sectional questionnaire survey from 618 rural youth entrepreneurs across seven wards in the Iramba District of Tanzania. Subsequently, structural equation modelling (SEM) was employed to assess the impact of FNI on the socio-economic outcomes of rural youth entrepreneurs. The study findings reveal a significant positive effect of FNI on rural youth economic empowerment, social capital and networking, access to healthcare and social services, and overall standard of living. The results provide actionable insights for policymakers, financial institutions, and development agencies aiming to foster entrepreneurship in rural areas. It highlights the importance of creating youth-tailored financial products, improving digital infrastructure, and enhancing financial literacy to boost the socio-economic impact of FNI in rural areas.